\( 04 / 02 / 2025 \) Exponents and surds Classwork Simplify the following expressions and leave answer with positive exponents. \[ \begin{array}{l} \text { 1. } 4 x^{9} \cdot 2 x^{-6} \\ 24^{n-1} \times 4^{1-n} \times 4^{2} \\ \text { 3 } \frac{9 x^{3} x^{2}}{1 \cdot x y^{4}} \\ \text { 4. }\left(3 x^{-3} \cdot y^{4}\right)^{-2} \\ \text { 5. } \left.2(x)^{-2}\right)^{3} \\ 6\left(\frac{x^{-1}}{y^{-1}}\right)^{-2} \\ \text { 1. } \left.\frac{2}{m^{2}}\right)^{-3} \\ \text { 8. } \frac{x^{\frac{3}{3}} \times x^{3}}{(x)^{4}} \\ \text { 9. } \frac{27 x^{-3} y^{-2}}{81 x^{2} y^{-3}} \\ \text { 10. } \frac{m^{3} n^{-6}}{m^{-4} n^{-1}} \times \frac{m^{-2} \cdot n^{4}}{m^{3} n^{4}} \end{array} \]
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
Sure! Let's simplify those expressions step by step while keeping the exponents positive. Here are the simplified answers for each expression. 1. \( 4 x^{9} \cdot 2 x^{-6} = 8 x^{3} \) 2. \( 24^{n-1} \times 4^{1-n} \times 4^{2} = 24^{n-1} \times 4^{3-n} = 12^{3(n-1)} \) 3. \( \frac{9 x^{3} x^{2}}{1 \cdot x y^{4}} = \frac{9 x^{5}}{y^{4}} = 9 x^{5} y^{-4} \) 4. \( \left(3 x^{-3} \cdot y^{4}\right)^{-2} = \frac{9 y^{8}}{x^{6}} \) 5. \( \left(2 x^{-2}\right)^{3} = 8 x^{-6} = \frac{8}{x^{6}} \) 6. \( 6\left(\frac{x^{-1}}{y^{-1}}\right)^{-2} = 6 \frac{y^{2}}{x^{2}} = \frac{6 y^{2}}{x^{2}} \) 7. \( \left(\frac{2}{m^{2}}\right)^{-3} = \frac{m^{6}}{8} \) 8. \( \frac{x^{\frac{3}{3}} \times x^{3}}{(x)^{4}} = \frac{x^{4}}{x^{4}} = 1 \) 9. \( \frac{27 x^{-3} y^{-2}}{81 x^{2} y^{-3}} = \frac{1}{3 x^{-5} y} = \frac{y}{3 x^{5}} \) 10. \( \frac{m^{3} n^{-6}}{m^{-4} n^{-1}} \times \frac{m^{-2} \cdot n^{4}}{m^{3} n^{4}} = \frac{m^{7} n^{-5}}{m^{-2} n^{0}} = m^{9} n^{-5} = \frac{m^{9}}{n^{5}} \) Now that we’ve simplified those expressions, let’s keep diving into some worthwhile suggestions to take your understanding ground-up!